Risk Management in Banks - Dhond, Arvind A. (SFIMAR Research Review, 2016)
In recent yea re, there has been a considerable widening and deepening of the Indian financial system, of which banking system is a significant component. With greater liberalization, the financial system has come to play a much larger role in the allocation of resources than in the past and its role in future can be expected to be much larger than at present. The growing role of the financial sector in the allocation of resources has significant potential advantages for the efficiency with which our economy functions. Consequently, the adverse consequences of malfunction of the financial system are likely to be more severe than they used to be in the past. Hence, all our efforts today are focused at ensuring greater financial stability. In order to achieve financial stability managing the risk is very much essential. Risk management is an inevitable part in almost every business in today’s world and banks are no exception to it. There are various types of risks which banks are facing namely liquidity risk, foreign exchange risk, market risk, credit risk and operational risk. Amongst all these risks credit risk, operational risk and market risks are the three important ma|or risks which banks have to face. Quality of risk management capabilities of a bank reflects in its profitability. With the increasing degree of deregulation and exposure of banks to various types of risks, efficient risk management systems have become essential. At the initial stages of development of the risk management systems, banks were managing each risk in isolation. The current business environment demands a more integrated approach to risk management. It is no longer sufficient to manage each risk independently or in functional departments. Enterprises worldwide are, therefore, now putting in place an integrated framework for risk management, which is proactive, systematic and spreads across the entire organization. Banks in India are also moving from the individual handling of risks system to an enterprise wide risk management system. Banks Risk Management Strategy should be a proactive risk management strategy ratherthan a reactive risk management strategy.